(untitled) (Ameghiniana, 2013)
In the regional geological survey out by the Instituto de Investigaciones Ceológicas de Chile (I.I.G.) was found out a lot of extensive deposits of marine sedimentary rocks of Upper jurassic age. These deposits show a great deal of outcrops that contains fossil fishes with a good preservation. This paper makes a preliminary description of a new species of the genus Leptole pis, denominated Leptolcpis opercularis.